Isolation and Full-Genome Characterization of Nipah Viruses from Bats, Bangladesh - Anderson, Danielle E.; Islam, Ariful; Crameri, Gary; Todd, Shawn; Islam, Ausraful; Khan, Salah U.; Foord, Adam; Rahman, Mohammed Z.; Mendenhall, Ian H.; Luby, Stephen P.; Gurley, Emily S.; Daszak, Peter; et al. (Emerging infectious diseases, 2019)
Despite molecular and serologic evidence of Nipah virus in bats from various locations, attempts to isolate live virus have been largely unsuccessful. We report isolation and full-genome characterization of 10 Nipah virus isolates from Pteropus medius bats sampled in Bangladesh during 2013 and 2014.